Evolution du profil physiologique des gymnastes durant les 40 dernieres annees - Jemni, M.; Friemel, F.; Sands, W.; Mikesky, A. (Canadian Journal of Applied Physiology, 2001)
Authors illustrate the evolution of the physiological profile of gymnasts over the past 40 years. Gymnasts are demonstrating increased anaerobic power. Maximal power output measured by the Wingate test in high level male gymnasts is currently between 12 and 14 W · kg-1. Female gymnasts show maximal power between 10 and 12 W · kg-1. In spite of an increase in the number of training hours, they have a low aerobic aptitude. It is still adequate and sufficient for their practice. Maximal heart rate values measured during gymnastic exercises have mirrored technical and acrobatic demands of increasing difficulty. Currently, exercise heart rates exceed 190 beat · min-1 as compared to 135 to 151 beat · min-1 in the seventies. Measurement of higher blood lactate values suggests that anaerobic glycolysis has increased in importance. Glycolytic contributions differ between apparatuses. Data from energy cost studies demonstrate that gymnastics energy demands are greater now than in the seventies.